2003
DOI: 10.1021/ol035147k
|View full text |Cite
|
Sign up to set email alerts
|

Sonogashira Coupling Using Bulky Palladium-Phenanthryl Imidazolium Carbene Catalysis

Abstract: [structure: see text] Bulky phenanthracenyl imidazolium-derived carbene ligands were investigated for copper-free Sonogashira coupling with terminal acetylenes. Aryl bromides and iodides gave coupled products in excellent yields from the Pd(PPh(3))(2)Cl(2) complex with potassium t-butoxide and 18-crown-6 in THF. A remarkable dependence on the size of the ligand was found. The highest yields were obtained with the bulky 2,9-dicyclohexyl-10-phenanthryl ligand 5.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(45 citation statements)
references
References 30 publications
0
41
0
4
Order By: Relevance
“…[154][155][156][157] Recent mechanistic work has shown that the oxidative addition of aryl halides to [PdL 2 ] (L = heterocyclic carbene = NHC) furnishes the expected trans square planar complexes (e.g. 21 and 22, Scheme 24).…”
Section: Heterocyclic Carbenes As Ligandsmentioning
confidence: 99%
“…[154][155][156][157] Recent mechanistic work has shown that the oxidative addition of aryl halides to [PdL 2 ] (L = heterocyclic carbene = NHC) furnishes the expected trans square planar complexes (e.g. 21 and 22, Scheme 24).…”
Section: Heterocyclic Carbenes As Ligandsmentioning
confidence: 99%
“…[200,201] Das wichtigste Reaktionsprotokoll nutzt Kupfersalze als Cokatalysatoren, meistens in Gegenwart von Aminbasen (Sonogashira-Reaktion). [201] [202] Unerwartet zeigte SIPr·HCl (13, Tabelle 1) nur moderate Aktivität. Kupferfreie Alkinkupplungen wurden auch von Herrmann et al [105] (mit 1 Mol-% 92) und von Cavell et al beschrieben (mit 0.1 Mol-% 280, Schema 66).…”
Section: Kreuzkupplungen Mit Alkinen Und Die Sonogashira-reaktionunclassified
“…83 The catalyst prepared in situ from the bulky imidazolium salt 235 and [Pd(PPh 3 ) 2 Cl 2 ] promoted the coupling of different iodo-and bromo-substituted arenes with terminal acetylenes. Surprisingly, the salt 214 showed only moderate activity.…”
Section: ç Sonogashira Reactionmentioning
confidence: 99%